Improving user content privacy on social networks using rights management systems - Marques, J; Serrão, C. (Annales des Télécommunications, 2014)
Currently, millions and millions of users are using online social networks to share their thoughts, experiences and content with online friends. Documents, videos, music and pictures are shared online, relying on the privacy and security controls offered by the social network platforms, with little control from the end user. This creates serious privacy concerns, since the control over the content shared online on the social network is out of the hands of the user. In this paper, the authors propose an approach for content privacy shared on social networks that is user-centric and not based on the social network platform. In order to achieve that, an architecture based on a rights management platform capable of enforcing the necessary security and privacy mechanisms that extend the original controls provided by the social network platform will be presented. That way, users will be able to control their privacy settings and protect their own content, even when they are no longer part of the social network (suspending or deleting its account).